Formalization of East Jerusalem public transport: Mobility, politics and planning. (December 2022) - Kerzhner, Tamara
Abstract: The integration and reform of small-scale public transport operators, often known as informal transport or paratransit, is increasingly a priority in managing urban mobility. In Jerusalem, city and national transport authorities have been working with Palestinian bus operators in East Jerusalem for over 20 years in an incremental formalization process that has seen both successes and ongoing challenges. Drawing on in-depth interviews with operators, regulators and community stakeholders, this study finds that the unification of small operators with long historical territories plays an important role in reform and service improvement. Operators and regulators are able to collaborate in order to improve services for passengers in areas such as safety, vehicle quality and some infrastructures. However, reforming route networks and enforcing level of service of remains difficult. In the context of Israel's ethnocratic municipal regime, the politics of reform are bounded in the history of the conflict, but also tied to bottom-up relationships between operators and communities. Highlights: Since 2000, reforms to the informal East Jerusalem system have seen improved vehicles, schedules, and driver training. Aspects of the process are stalled despite operators and regulators interest, including routing and ticketing integration. Semi-formal firms maintain close community and historical ties to set operating areas, and are reluctant to change them. Formal regulators are unable to integrate such non-economic concerns fully into their understanding of the reform process. Firms better able to match the codes of the formal, regulatory state can reap some benefits, while others fall behind.